Vibration measurement of a micro-structure by digital holographic microscopy - Shi, Hongjian (2011)
A method for the vibration measurement of a micro-electro-mechanical system (MEMS) structure based on digital holographic microscopy (DHM) is presented. A sequence of digital holograms of a vibrating micro-beam excited by varying voltage is captured by a high-speed CCD camera. The phase changes of the object at different instants are obtained by digital reconstruction.